IPA 기반의 공적개발원조 건설사업 역량 분석 - 김화랑; 정민철; 장현승; Kim, Hwarang; Jung, Mincheol; Jang, Hyounseung (한국건설관리학회 논문집, 22(5), 2021)
Participation in official development assistance (ODA) construction projects can be proposed as a way to revitalize Korean small and medium-sized construction companies' entry into the overseas construction market. To this end, the necessary competency items were derived for the execution of the project, and a survey was conducted and an analysis of importance-current competency was performed. 24 out of a total of 32 competency items were analyzed as having a low level of competency compared to their importance, indicating that it is urgent to strengthen corporate-level capabilities for the smooth execution of related projects in the future. In detail, it is judged that it is necessary to seek to establish a preferential capacity-strengthening plan for contract management-related items such as the 'Construction-related fundamental laws, Contract management method, and International administration negotiation'. 우리나라 중소건설기업의 해외건설시장 진출 활성화 방안으로 공적개발원조(ODA) 건설사업 참여를 제안할 수 있다. 이를 위해 해당 사업수행 시 필요한 역량 항목을 도출하였으며 이에 관한 설문조사 수행과 중요도-현재 역량 분석을 수행하였다. 총 32개의 역량 항목 중 24개 항목이 중요도 대비 현재 역량 수준이 낮은 것으로 분석되어 향후 원활한 관련 사업수행을 위한 기업 차원의 역량 강화가 시급한 것으로 나타났다. 세부적으로는 '건축 관련 기본법, 계약관리 방법, 국제경영협상' 등 계약관리 관련 항목에 관한 우선적 역량 강화방안 수립의 모색이 필요할 것으로 판단된다.